Rationale for combining immunotherapy with chemotherapy. (March 2015) - Dalgleish, Angus G
Immunotherapy has usually been considered as an alternative to more traditional modalities. Moreover, it has previously been felt that chemotherapy is inherently immunosuppressive and not suitable for combining with immunotherapy. In this review, the concept of combining different modalities that result in cell death, such as radiotherapy and chemotherapy, with immunotherapy is explored. Tumors actively cause immune suppression which can be reversed by their removal but when this is not possible, enhancing the immune response with nonspecific immune stimulation can enhance the response to other modalities, such as radiotherapy and chemotherapy. Additionally, several chemotherapy agents at low doses selectively inhibit regulatory and suppressor cells.